Proximate and Microbial Analysis of Yellow, White and Spoilt Garri Sold in Owerri, Imo State, Nigeria - Udensi J. U.,; Anyanwu C. O.,; Opara M. C.,; Egwuogu G. C.,; Duru C. C.,; Anyanwu E. C.,; Nwanaforo E. O., (Archives of Current Research International, 2024)
This study explored the proximate and microbial composition of garri, a widely consumed starchy food in West Africa, particularly in Nigeria, Ghana, and neighboring countries. Garri, derived from cassava, is esteemed for its extended shelf life, cost-effectiveness, and nutritional value, holding a significant place in West African diets. Samples of yellow and white garri, including spoilt variations, were procured from four distinct local markets (Obinze, Relief, Eke Ukwu, and Ihiagwa) and subjected to thorough analysis using standard methods. Proximate analysis encompassed key components such as ash content, moisture, fiber content, lipids, protein, carbohydrates, and energy in both white and yellow garri from different markets. White garri exhibited a higher ash content (1.70±0.58%) than yellow garri (1.27±0.24%). Moisture content was greater in white garri (15.74±0.23%) compared to yellow garri (12.55±0.57%). Fiber content was 9.12±0.23% in yellow garri and 8.018±0.09% in white garri. Lipid content was 0.33±0.46% in yellow garri and 0.09±0.18% in white garri. Protein content showed values of 0.50±0.89% for yellow garri and 0.66±0.38% for white garri. Carbohydrate content was 76.91±0.71% in yellow garri and 74.91±0.067% in white garri. Energy content (kJ/100g) was 960.59±0.93 for yellow garri and 1268.18±0.39 for white garri. Microbial analysis conducted on the samples from each market revealed bacterial load of various ranges. Fresh white garri bacterial loads ranged from 3.25±0.83 log10 CFU/g (Ihiagwa) to 3.93±0.67 log CFU/g (Eke Ukwu). Fresh yellow garri bacterial loads ranged from 2.27±0.43 log CFU/g (Ihiagwa) to 2.92±0.54 log CFU/g (Eke Ukwu). Statistical analysis indicated no significant difference (P>0.05) in bacterial loads between white and yellow garri. Spoilt white garri bacterial loads ranged from 5.27±0.56 log CFU/g (Ihiagwa) to 5.93±0.43 log CFU/g (Eke Ukwu), and a similar trend was observed for spoilt yellow garri (5.34±0.46 log CFU/g to 5.95±0.16 log CFU/g). The study identified bacteria isolates, including Bacillus spp, Staphylococcus spp, and Streptococcus spp. This study underscores the importance of educating producers and sellers on proper processing and handling procedures to enhance the microbial quality and safety of garri products. The high microbial load and presence of some pathogenic microorganisms in the garri samples should serve as great eye-opener to the consumers of raw garri.